Analysis and evaluation of vibration characteristics of a new type of electric mini-tiller based on vibration test - Niu, Po; Chen, Jian; Zhao, Jingdou; Luo, Zeyong (International Journal of Agricultural and Biological Engineering, 2019)
Now the internal combustion engine mini-tiller has become the main and indispensable agricultural machinery in vast hilly and mountainous areas of Southwest China. However, its intense vibration may pose a big threat to operators. As a countermeasure to the tiller vibration, a new type of electric mini-tiller powered with a group of lithium battery and a brushless DC motor was developed. The vibration signals at the handle of the tiller were tested under 6 conditions as follows: the tiller was under states of static and working in the field, at slow, medium and rapid speed, respectively. The signals were processed by means of the time domain eigenvalue analysis and the frequency spectrum analysis. The results show that with the electric motor rated speed increased from 95 to 140 r/min under static conditions, the RMS values increased 122.54%, and with the forward speed increased from 0.30 to 0.80 m/s under working conditions, the RMS values increased 201.78%. When the tiller was working, the first order vibration frequencies were 25.99 Hz, 26.99 Hz and 28.99 Hz at slow, medium and rapid speed respectively, all not within 37.50-65.00 Hz, the sensitive range of human hands to the vibration frequency. In addition, according to the results of hand transmitted vibration analysis, it can be found that compared with operating the internal combustion engine mini-tiller under the same working condition, the onset of vibration-induced white finger can be delayed for 3.70 years to 10.20 years by operation of the new electric tiller. Keywords: electric mini-tiller, vibration characteristics, time domain analysis, frequency domain analysis, hand transmitted vibration DOI: 10.25165/j.ijabe.20191205.4737 Citation: Niu P, Chen J, Zhao J D, Luo Z Y. Analysis and evaluation of vibration characteristics of a new type of electric mini-tiller based on vibration test. Int J Agric & Biol Eng, 2019; 12(5): 106–110.